Identifikasi Miskonsepsi Siswa Menggunakan Test Diagnostic Five Tier Multiple Choice pada Materi Reaksi Redoks di SMAN 1 Limboto - Ibrahim, Sufriyanto; Mohamad, Erni; Munandar, Haris; Pikoli, Masrid; Kunusa, Wiwin Rewini; Tangio, Julhim S.; Kurniawati, Erga (CV. ULIL ALBAB CORP, 2024)
Redox reactions are a type of chemical material that contains many concepts and rules that are recognized as difficult to comprehend and comprehend and often give rise to misconceptions in students. This research aims to find out the misconceptions that occur among students in understanding redox reaction material and find out the source of the causes of students' misconceptions. The method used in the research is descriptive qualitative. This research was carried out in the odd semester of the 2023/2024 academic year. The subjects of this research were class XII MIPA students at SMAN 1 Limboto with a total sample of 181 people. Identification of misconceptions is carried out using a five-tier multiple-choice test instrument. Student answers from the test are then analyzed and categorized based on the student's level of conception. The research results show that the average percentage of students' conceptions on redox reaction material is 28.6% understanding the concept, 48.2% misconceptions, and 23.2% not understanding the concept. Apart from that, the highest cause of misconceptions comes from personal thoughts at 91.1%.